Pruning type and timing affect agronomic performance of blueberry plants grown in central Brazil - Miranda, Gabriel Soares; Nunes de Lima, Firmino; Kiyoshi Yamanishi, Osvaldo; Ricardo Peixoto, José; De Carvalho Pires, Márcio (Comunicata Scientiae, 2025)
Global blueberry production more than quadrupled between 2010 and 2022. One of the factors contributing to this production growth was the development of new cultivars with little or no chilling requirements, capable of thriving in tropical regions. Therefore, the objective of this study was to assess the growth and fruit yield of blueberry plants (Biloxi cultivar) subjected to different pruning types and timings in the Distrito Federal (DF), Central-West region of Brazil. The experiment was conducted in an open field, using a randomized complete block design with 3 replications and 10 plants per plot, totaling 480 plants. The plants were grown in pots using a fertigation system and were subjected to two types of pruning (severe pruning and regular pruning) in the different seasons of the year. The plants were evaluated for vegetative growth, fruit yield, number of fruits per plant, mean fruit weight, and fruit transverse and longitudinal diameters. The results showed that Biloxi blueberry can be grown under the climate conditions of the central region of Brazil, during the four seasons of the year, despite the tropical climate conditions and no occurrence of temperatures lower than 7.2 °C. Higher fruit yields were found when pruning was performed in winter or spring. Severe pruning resulted in higher fruit yields compared to regular pruning in winter. Summer and autumn pruning treatments reduced fruit yield; however, it is an alternative to extend the production window of this crop in Brazil.